Why gradual and predictable? Bank lending during the sharpest quantitative tightening ever - Lorenzo Burlon; Alessandro Ferrari; Stephen Kho; Nikoleta Tushteva (European Central Bank (ECB), 2025)
Exploiting the recalibration of ECB's outstanding central bank funding in 2022, we show that a sharp reabsorption of bank liquidity induces a tightening impact on credit supply, as intended when central banks reduce their balance sheets. The tightening originates from the sudden relative convenience for banks accustomed to large liquidity holdings to more rapidly adapt to the new environment. Moreover, we show that the associated reduction in credit supply has real economic effects.
Keywords: E51; E52; G21; 330; monetary policy; banking; credit supply; QT; liquidity